Legal Regulations and Implications of Building Use Rights on Land Management Rights for Public Assets - Calista , Jessica; Djaja, Benny (Dinasti Research, 2024)
This article is entitled the regulation and legal implications of building use rights over land management rights for public assets. Using legal research methods with normative research types, using statute research approaches and conceptual approaches . With the results of the analysis, the regulation regarding HGB above HPL has undergone changes which were previously regulated in PP No. 40 of 1996 concerning Cultivation Rights, Building Use Rights and Use Rights are now regulated in PP No. 18 of 2021 concerning Management Rights, Land Rights, Flats and Land Registration . Conformity of HGB above HPL regulations in PP No. 18 of 2021 with the UUPA it can be said that there is no synchronization and harmonization, where in the UUPA the procedures for extending and renewing HGB must be carried out in stages and according to requirements, the land is still used and utilized properly according to the circumstances, nature and the purpose of granting rights and must obtain approval from the HPL holder. Even though in the provisions of PP no. 18 of 2021 also determines the same thing, but the provisions of Article 41 paragraph (3), especially for HGB, allow that after being granted SLF, rights can be extended and renewed.